Selection for muscling in Durocs - Wheat, J.D.; Kropf, Donald H.; Na-Lampang, P.; Hines, Robert H. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Select line pigs were compared with those in the control line for growth patterns, production traits, and carcass quality. Heritability and genetic correlations were calculated for certain production and carcass traits after five generations of selection.
Keywords: Swine; Muscling; Durocs